O-261 In-vitro supplementation of vitamin B12 to improve post-thaw viability and DNA integrity. (30th June 2022) - Yuvaraj, S; GopalaKrishnan, M; Reddy, S; Vembu, R; Namboori Srinivasan, S; Raja, N; Pandurangi, M; Nagireddy, S; Raman, G; Rajmohan, L; Ramamoorthy, S; Kumar, V
Abstract: Study question: Does the supplementation of vitamin B12 protect the spermatozoa against damage caused by the freeze-thaw process further improving the overall post-thaw survival and DNA integrity? Summary answer: The antioxidant property of vitamin B12 protects the spermatozoa and improves the post thaw motility, vitality, and reduces DNA damage caused by freeze-thaw process. What is known already: Cryopreservation of spermatozoa is an effective way of fertility preservation in humans, often used in Assisted Reproductive Technology(ART). Despite the refinement in cryopreservation, the salvage of post-thaw sperms remains poor. The reactive oxygen species(ROS), that is formed as a result of freeze-thaw process is known to decrease the motility, plasma membrane integrity and increase the DNA fragmentation. Most vitamins have antioxidant properties, that protect the mammalian cells from oxidative stress one such vitamin is cyanocobalamin(vitamin B12). Vitamin B12 modulates oxidative stress through methionine synthase activity and also acts as a scavenger of ROS. Thus protecting the DNA against free radicals. Study design, size, duration: This prospective observational study was performed for a period of 6 months in 111 men, who attended the fertility clinic. The study population included all semen samples except men with azoospermia, surgically retrieved samples and men on vitamin supplements. The study population contained men ageing between 21-40 years. Participants/materials, setting, methods: Semen samples were analysed according to WHO 5 th edition and were assessed for DNA fragmentation index (DFI) using sperm chromatin dispersion assay (SCD). The ejaculates were split into two as group A: semen samples with equal amount of cryoprotectant and group B: semen samples with equal amount of cryoprotectant supplemented with Vitamin B12 (2mg/ml). They were frozen for a minimum of 24 hrs. Post-thaw motility, vitality and DFI were assessed and compared. Main results and the role of chance: The mean age of patients in our study was 34.26±4.7yrs. 58.5% of the study population had primary infertility. 37.8% of the study population had male factor infertility, 32.4% had oligoasthenoteratozoospermia(OAT), 31.1% had normozoospermia 16.2% had asthenoteratozoospermia, 13.5% had teratozoospermia, 3.6% had oligozoospermia and rest 2.7% had asthenozoospermia. There was an overall increase in post thaw motility (41.59±18.09 vs 32.3±18.8, p=0.0005), progressive motility (21.54±13.02 vs 15.91±11.80, p=0.0005), vitality (57.14±15.09 vs 46.76±16.45, p=0.0005) and a significant decrease in DFI (26.69±10.03 vs 32.09±10.00, p=0.0005) in group B compared to group A. Our study also demonstrated that, Normozoospermia patients had a significant increase in vitality (67.17±13.8 vs 58.51±12.0, p = 0.007) and lower DFI (22.68±9.3 vs 27.6±8.9, p = 0.02) in group B than in group A. OAT patients had a significant increase in total motility (26.25±12.15 vs 15.7±11.4, p=0.0003), progressive motility (11.69±8.8 vs 6.14±5.8, p=0.0028), vitality (46.06±11.34 vs 34.31±12.99, p=0.0001) and significantly lower DFI (30.22±9.87 vs 36.08±9.7, p=0.012) in group B. Teratozoospermia patients showed significant increase in progressive motility in group B (27.87±8.81 vs 19.33±10.69, p=0.02) and Asthenoteratozoospermia patients showed significant increase in total motility (40.72± 13.14 vs 30.89±13.06, p=0.02) and vitality (54.39±12.28 vs 43.78±14.14, p=0.02) in group B. However, in asthenozoospermic patients the parameters were comparable in both the groups. Limitations, reasons for caution: Due to ethical reasons the samples were not used for in vitro procedures such as intrauterine insemination(IUI), in vitro fertilization (IVF) and intracytoplasmic sperm injection(ICSI). Hence, no inference was obtained regarding the fertilization rates/ pregnancy rates. Wider implications of the findings: Our study demonstrated that with supplementation of vitamin B12 the recovery rate significantly increased and also preserved the DNA content. Among the various categories, supplementation of vitamin B12 to OAT samples was more beneficial as it improved the overall viability of the sperms. Trial registration number: CSP/21/JUL/96/389